The Efficacy of Collaborative Governance in Waste Management: Evidence from Bandung Village, Kebumen Regency, Central Java - Martitah, Martitah; Sumarto, Slamet; Pujiono, Pujiono; Hidayat, Arif; Putra, Tegar Islami; Aini, Triska Rahmatul (Indonesian Journal of Legal Community Engagement, 2025)
The Central Java Province contains five significant slums focus, contains Sukoharjo Regency, Wonosobo Regency, Banjarnegara Regency, Brebes Regency, and Kebumen Regency. Kebumen Regency is one among the regions with a notable slum area. This community service aims to identify strategies to enhance the efficacy of the district village legislator (BPD) and village administration in waste management via village regulation, focusing on a case study of Bandung Village, Kebumen Regency. This community service utilizes direct counseling as its methodology. The community service outcomes indicate that the BPD and the Village Government in Bandung Village, Kebumen, collaborate effectively in waste control through the formulation of Village Regulations. The BPD formulates legislation and oversees the community, whereas the Village Government administers technical implementation and engagement. Participatory procedures, the establishment of waste banks, and the principles of transparency and accountability are essential for the efficacy of sustainable waste management in this context.